Ikhlas, Lepas, Tuntas : Interpretative Phenomenological Analysis tentang Pengalaman Perempuan Korban Toxic Relationship dalam Berpacaran - Syerli Akhla Rosa; Alifia Putri Fadilah Sati; Anisa Resa Savitri; Rafly Rafly; Sakinatun Hasanah; Ulfa Dwina (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
A toxic relationship is an unhealthy relationship between a man and a woman, which generally causes psychological and physical discomfort. This study focused on women as victims of toxic relationships, with semi-structured interviews with two female participants who experienced toxic relationships. Aiming to find out the description of the experiences of women victims of toxic relationships, with the uniqueness of each participant, then be analyzed using Interpretative Phenomenological Analysis. The results found five main themes: toxic behavior; motivation to maintain relationships; the impact of a toxic relationship; self- awareness; hope. The unique theme that emerged in the participants was a complex form of violence in the second participant which was influenced by the duration of the relationship including physical, psychological, economic violence and other things. The findings in this study can be a lesson especially for people who are dating to be more aware of the health of the relationship that is being undertaken.